ABDURRAHMAN WAHID DAN PRIBUMISASI PENDIDIKAN ISLAM - Hadi, M. Khoirul (Hunafa: Jurnal Studia Islamika, 2015)
This article examines Abdulrahman Wahid and his thoughts on the indigenization of Islamic education. The approach used is content analysis to examine the works Abdurahman Wahid, and the historical approach to study his biography. The results showed: first, education indigenization of Islam according to Wahid , mengedapankan more substantive learning, where the education was no tolerance values, local culture-based education and Islamic education rahmatan li al- Alamin. Second, a good religious education is education that adapts to local culture, non-formal religious education in the surrounding communities and that indigenization Islamic education desired by K.H. Abdurahman Wahid.